Ocean : a history of the Atlantic before Columbus - Haywood, John, 1956- (Pegasus Books, 2024)
This work is a comprehensive cultural history of the Atlantic Ocean before Columbus, tracing its development from geological formation and the rise of early humans to the advancements in shipbuilding, navigation, and maritime exploration. It delves into the origins of the transatlantic slave trade and the early stages of European imperialism, offering a broad overview of the forces shaping this crucial body of water and its global significance.